Functional analyses of the UDP-galactose transporter SLC35A2 using the binding of bacterial Shiga toxins as a novel activity assay. (11th April 2019) - Li, Danyang; Mukhopadhyay, Somshuvra
Abstract: SLC35A2 transports UDP-galactose from the cytosol to the lumen of the Golgi apparatus and endoplasmic reticulum for glycosylation. Mutations in SLC35A2 induce a congenital disorder of glycosylation. Despite the biomedical relevance, mechanisms of transport via SLC35A2 and the impact of disease-associated mutations on activity are unclear. To address these issues, we generated a predicted structure of SLC35A2 and assayed for the effects of a set of structural and disease-associated mutations. Activity assays were performed using a rescue approach in Δ SLC35A2 cells and took advantage of the fact that SLC35A2 is required for expression of the glycosphingolipid globotriaosylceramide (Gb3), the cell surface receptor for Shiga toxin 1 (STx1) and 2 (STx2). The N- and C-terminal cytoplasmic loops of SLC35A2 were dispensable for activity, but two critical glycine (Gly-202 and Gly-214) and lysine (Lys-78 and Lys-297) residues in transmembrane segments were required. Residues corresponding to Gly-202 and Gly-214 in the related transporter SLC35A1 form a substrate-translocating channel, suggesting that a similar mechanism may be involved in SLC35A2. Among the eight disease-associated mutations tested, SLC35A2 function was completely inhibited by two (S213F and G282R) and partially inhibited by three (R55L, G266V, and S304P), providing a straight-forward mechanism of disease. Interestingly, the remaining three (V331I, V258M, and Y267C) did not impact SLC35A2 function, suggesting that complexities beyond loss of transporter activity may underlie disease due to these mutations. Overall, our results provide new insights into the mechanisms of transport of SLC35A2 and improve understanding of the relationship between SLC35A2 mutations and disease.